The Election of a Fringe Candidate: Anomalous or Normal? The Arrival of Donald Trump to the White House in 2016 - Álvarez del Castillo Calderón, Carlos (2022)
Donald Trump’s 2016 successful electoral bid came as a surprise both to the public and pundits. Soon after the upset election, conventional wisdom settled on an explanation: that Trump’s victory was linked to Americans that felt left behind by globalization and the current political establishment. Conventional wisdom provided quick and straightforward answers. Nevertheless, these answers were incomplete. Chief among the missing elements of the improvised explanation was the radicalization of the Republican party. To fully understand how the transformation of the Republican Party resulted in President Trump’s election and his foreign  policy, this article will analyze the case through constructivist lenses. According to this perspective, identity plays a crucial role in both domestic and international politics. By providing an analysis of American identity and especially of the identity of the Republican Party, constructivism provides useful knowledge in the interpretation of both Trump’s election and his administration’s foreign policy. We argue that what really explains Trump victory in the electoral college in the November 2016 electoral process (he lost the popular vote by about three million votes) are ideational, identity-related factors—not his personality or the globalization-related arguments conventional wisdom focuses on.